# Pre-calculus need help!!

1.) x+6/x=-7
2.) 4x/x+4 + 3/x-1 = 15/x^2+3x-4
3.) x+3/x - 2/x+3 = 6/x^2+3x

formula:
-B+ sqrt B^2 + (-4)(a)(c)/2a
f u only wanted to use the formula it's not necessary though.

x = (-b ± √(b^2 - 4ac) )/(2a)

1. x + 6/x = -7
each term by x

x^2 + 6 = -7x
x^2 + 7x + 6 = 0
it factors, no need for the formula
(x+1)(x+6) = 0
x = -1 or x = -6

2. you probably meant:
4x/(x+4) + 3/(x-1) = 15/(x^2 + 3x - 4)
4x/(x+4) + 3/(x-1) = 15/((x-1)(x+4) )
multiply each term by (x+4)(x-1) , the LCD
4x(x-1) + 3(x+4) = 15
4x^2 - 4 + 3x + 12 = 15
4x^2 + 3x -7 = 0
x = (-3 ±√(9-4(4)(-7)) )/8
= (-3 ±√121)/8 = (-3 ± 11)/8
x = 1 or x = -7/4

or.... we could have factored it again
(x-1)(4x + 7) = 0
x = 1 or x = -7/4

3. again, brackets will be essential.
(x+3)/x - 2/(x+3) = 6/( x(x+3))
the LCD is x(x+3) , so multiply each term by x(x+3)
You can take it from there.

posted by Reiny

## Similar Questions

1. ### Math

Use the quadratic formula to solve each of the following quadratic equations... 1. 2x^2-5x=3 2. 3x^2-2x+1=0 Rearrange the equation in quadratic formula form. 2x^2 -5x -3 = 0 Then use the formula. Tell me what you don't understand
2. ### math,algebra

can someone help me out factor out this 0=16t^2-122t+180 i have so far this but the last one i am not sure 8(2t^2-14t + ?) you need to use the quadratic formula: -b(+or-)[sqrt(b^2-4ac)/2a] so you are saying that i don't have to
3. ### Math

Solve for the zeros of the function using the quadratic formula. 3x^2=-4x+6 I know what the quadratic formula is but when I put it into the formula I keep getting an error on the graphing calculator.
4. ### Calculus

Please look at my work below: Solve the initial-value problem. y'' + 4y' + 6y = 0 , y(0) = 2 , y'(0) = 4 r^2+4r+6=0, r=(16 +/- Sqrt(4^2-4(1)(6)))/2(1) r=(16 +/- Sqrt(-8)) r=8 +/- Sqrt(2)*i, alpha=8, Beta=Sqrt(2) y(0)=2,
5. ### math

use the quadratic formula to solve this equation. 4x^2-8x+3=5 use the formula x=-b + or - the sqrt of b^2-4ac/2a yes, the 2a divides into all. Memorize it.
6. ### math

15t^2+7t=2 The quadratic formula tells you that the solutions are: t = [-b +/-sqrt (b^2 - 4ac]/ (2a) In this case, a = 15, b = 7 and c = -2 solve the equation for t. What values for t will you get when you substitute the values
7. ### Pre-Algebra

Please help to solve to find x,y 1. y=7x-3 2. 4x+2y=8 Take the value of y in the first formula and substitute it for y in the second formula. Solve the second formula for x. Once x is found, solve for y in the second formula.
8. ### Ap algebra

2+3X^2-X^3=0 by use quadratic formula. The answer of textbook is 3.19 So I solved and came out a wrong answer What I did factor out (-X+3)X^2+2=0 Then By quadratic formula, a=1,b=0,c=2. Thus I got sqrt(8)/2
9. ### math-calculus

solve equation |x^2-2x-6| using quadratic formula. i not get how to do this and it says quadratic formula.
10. ### algebra

I worked the problem out, but could you check my work over and see if it's correct? I used the quadratic formula. 2x^2+10x+11 a=2 b=10 c=11 x=-10(plus or minus) sqrt 10^2-4(2)(11) over 2(2) -10(plus or minus) sqrt 100 - 8(11) over

More Similar Questions